Similarities and differences between two Hungarian particles for also: szintén and is - Farkas, Judit; Futó, Bettina; Huszics, Aliz; Kleiber, Judit; Dóla, Mónika; Alberti, Gábor (LingBaW. Linguistics Beyond and Within, 2020)
The paper provides a comparative analysis of the syntax, semantics and pragmatics of two Hungarian particles with the same logical core meaning also: is and szintén. The analysis yields important theoretical implications since it demonstrates how two particles sharing the same logical-propositional/truth-functional core meaning can expand into two different markers. In discourse, is acts as an intensional/metacognitive pragmatic marker in the sense as proposed by Aijmer et al. (2006), while szintén functions as a coherence-signaling discourse marker. The two particles share certain syntactic-semantic properties: neither of them can be followed by a topic, they both have distributive meaning, and both of them can pertain to the noun phrase that they immediately follow, as well as to ordered n-tuples of noun phrases. However, there are also syntactic and pragmasemantic differences between them. Namely, their ordered n-tuples have different word orders; is can function as a pragmatic marker while szintén cannot; szintén can appear as a separate clause, while is cannot (this is presumably related to the fact that szintén can be stressed, while is is obligatorily unstressed); and finally, szintén can have a peculiar discourse-preserving function. We explain the syntactic differences between the two particles using the partial spell-out technique of minimalist generative syntacticians (first applied to Hungarian by Surányi 2009), and the Cinque-hierarchy-based approach to Hungarian sentence- and predicate-adverbials (Surányi 2008). We account for the pragmasemantic properties of the pragmatic-marker variant of is in the formal representational dynamic theory of interpretation called ReALIS, already presented in the LingBaW series (Alberti et al. 2016, Kleiber and Alberti 2017, Viszket et al. 2019).